2015
DOI: 10.1177/0021998315602324
|View full text |Cite
|
Sign up to set email alerts
|

Carbon fibre-reinforced poly(ethylene glycol) diglycidylether based multifunctional structural supercapacitor composites for electrical energy storage applications

Abstract: We have developed structural supercapacitors that can carry mechanical loads as well as can store electrochemical energy simultaneously. Structural supercapacitors are fabricated by impregnating carbon fibre mat electrodes and glass fibre mat separator with crosslinked poly(ethylene glycol) diglycidylether polymer electrolyte using the resin infusion under flexible tooling method. In this study, design parameters of the structural supercapacitors have been explored including the separators and the polymer elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 40 publications
2
32
0
Order By: Relevance
“…The capacitive performance is generally not 'state-of-the-art' for structural supercapacitors, mainly because of the high resistance of the electrolyte matrix. Despite this, the capacitances of our electrode materials are still comparable with other recent studies [12,30]. It is important to note that to maximize the mechanical properties of the composite, a stiff matrix is required to give sufficient stress transfer to the fibres.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The capacitive performance is generally not 'state-of-the-art' for structural supercapacitors, mainly because of the high resistance of the electrolyte matrix. Despite this, the capacitances of our electrode materials are still comparable with other recent studies [12,30]. It is important to note that to maximize the mechanical properties of the composite, a stiff matrix is required to give sufficient stress transfer to the fibres.…”
Section: Discussionsupporting
confidence: 72%
“…that an increase in the EMITFSI concentration results in increased ionic conductivity but decreased compression strength of PEGDGE electrolytes [30]. Similarly, in our study, the increased R s at 24 h compared to 2 h of curing of the electrolyte matrix also suggested that the higher degree of cross-linking is not good for the electrocapacitive performance.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Moreover, the supercapacitors have long cycle life of tens of thousands of charge–discharge cycles. 14 The repeated charge–discharge cycles of the fabricated structural supercapacitors, with as-received CF electrodes, have been previously investigated, 41 and the structural supercapacitors showed excellent reversibility of charge storage process.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to that, the size and concentration of electrolyte ion and electrolyte stability are also crucial factors. The glass fiber was reported as good separator material when considering both electrochemical and mechanical perspectives . In this process, therefore, the 1 layer of glass fiber was sandwiched into 2 prepared hybrid SnO 2 ‐WCF electrodes as separator.…”
Section: Methodsmentioning
confidence: 99%